Reading Attitudes of Bachelor of Business Administration (BBA) Students with Bengali Medium Background at the Bangladeshi Private Universities in Dhaka City (Journal of Business and Technology (Dhaka), 2017)
The study basically aims at uncovering the reading attitudes of the Bachelor of Business Administration (BBA) students of the Bangladeshi English medium private universities. It has been observed that the private university students, coming from Bengali-medium colleges, read very little in English and consequently they hardly grow up as better readers. The study has used both quantitative and qualitative methods. For collecting quantitative data, a structured questionnaire was administered among the sampling respondents, 120 BBA students from six private universities located in Dhaka city, selected using simple random sampling procedure. On the contrary, for gathering qualitative data, the researcher depended on a number of classroom observations, focus group discussions (FGDs) that took place among 20 different BBA students divided into two groups, and teacher interviews (10 teachers). It is revealed from the study that the students have mixed attitudes towards reading. In some cases, they have been found enthusiastic readers who read due to their passion for reading or for having pleasure out of reading. However, in many cases, they have affirmed that they become anxious and bored of extensive reading. Besides, they mainly read for passing the examinations or obtaining good grades. Finally, it has been unearthed that both teachers and reading materials play vital roles in developing learners reading attitudes.Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 91-110